The Analysis of Digital Marketing Strategy of Starbucks in Shanghai, China - Lin, Yao; Trianasari, Trianasari (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2025)
This study examines Starbucks' marketing strategies in China, within a dynamic competitive landscape and the evolving post-COVID-19 consumer behavior. Using a descriptive research design, data was collected through interviews and document analysis, supplemented by a survey of 69 participants. The study explores Starbucks' localization strategies, challenges from local competitors, and the impact of global events on its operations. Theoretical frameworks such as the 4P Marketing Theory, Gratifications Theory, Global Marketing Strategy, Motivation Needs Theory, Value Chain Analysis, and the RACE model guided the analysis. The findings indicate strong brand loyalty driven by effective digital marketing and local adaptation, though pricing remains a key concern for consumers. Thematic analysis identified eight key themes influencing Starbucks' success, including customer engagement and technological integration. While Starbucks has successfully localized its offerings, further enhancements in personalization and pricing strategies are recommended. The study suggests future research on customer segmentation, emerging technology applications, and corporate social responsibility initiatives to strengthen market competitiveness. These insights provide valuable implications for Starbucks to sustain its market position and drive continued growth in Shanghai’s evolving consumer landscape.